2020
DOI: 10.1111/cas.14355
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA binding proteins for cancer therapy

Abstract: Yoshitomo Shiroma and Ryou-u Takahashi contributed equally to this work.Abbreviations: AEP, AF4 family/ENL family/P-TEFb; ARNT, aryl hydrocarbon receptor nuclear translocator; BRD4, bromodomain-containing protein 4; CBP, CREB-binding protein; DUX4, double homeobox protein 4; ETO, eight-twenty one; EWS, Ewing's sarcoma; FLI1, friend leukemia virus integration 1; HIF, hypoxia-inducible factor; MLL, mixed-lineage leukemia; SOX2, Sry-related high-mobility box 2; STAT3, signal transducer and activator of transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 65 publications
2
28
0
Order By: Relevance
“…Recent studies have elucidated that somatic mutations and chromosomal abnormality can cause and promote tumorigenesis and progression, in which TFs are considered as driver genes ( Dang, 2012 ; Yokoyama, 2017 ). In fact, developing inhibitors that can suppress the activity of dysregulated TFs has been a promising approach for tumor-targeted therapy ( Shiroma et al, 2020 ). Shiroma et al (2020) and Qian et al (2020) have reviewed the small-molecule selective inhibitors that target cancer-associated TFs in both blood tumors and solid tumors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have elucidated that somatic mutations and chromosomal abnormality can cause and promote tumorigenesis and progression, in which TFs are considered as driver genes ( Dang, 2012 ; Yokoyama, 2017 ). In fact, developing inhibitors that can suppress the activity of dysregulated TFs has been a promising approach for tumor-targeted therapy ( Shiroma et al, 2020 ). Shiroma et al (2020) and Qian et al (2020) have reviewed the small-molecule selective inhibitors that target cancer-associated TFs in both blood tumors and solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of transcription is complex, and transcription is finely regulated by multiple participants, including transcription factors (TFs) ( Yevshin et al, 2019 ). TFs account for ∼8% of all human genes, and they can regulate target gene expression through specific recognizing and binding to the corresponding promoter or enhancer region ( Lambert et al, 2018 ; Yevshin et al, 2019 ; Qian et al, 2020 ; Shiroma et al, 2020 ). Lambert et al (2018) systematically identified and functionally characterized 1,639 human TFs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations